EVALUASI BUTIR SOAL SECARA KLASIK DALAM EVALUASI PENDIDIKAN - Achmad Rasyid Ridha; Moh Luthfi; Mudijono (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Item analysis plays a crucial role in educational evaluation to ensure that assessment instruments are valid, reliable, and fair. This study discusses the application of Classical Test Theory (CTT) in analyzing the quality of test items, particularly in the evaluation of Islamic Education (PAI) learning. The analysis focuses on item difficulty index, discrimination index, distractor effectiveness, and test reliability. A quantitative approach was employed by analyzing students’ test response data using classical item analysis procedures that can be implemented through simple tools such as Microsoft Excel. The discussion indicates that classical item analysis effectively identifies high-quality items as well as items that require revision or elimination. Moreover, this approach is considered practical, economical, and easy to apply for teachers, especially within the context of the Independent Curriculum (Kurikulum Merdeka). Despite its limitations, including sample dependency, Classical Test Theory remains a relevant and effective method for improving the quality of assessment and learning outcomes in Islamic Education.